Mastosit Perivaskuler Berperan Sebagai Vasodilator Pembuluh Darah pada Mesenterium Tikus - Ibrahim, Mohamad Nur; Soleh, Miftahu; Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2009)
Mastocyt  degranulated  can  cause  vasodilatation  of  blood  vessels,  but  it  is  unclear  whether  there  is  a relationship  between the  number of mastocyt with a diameter of blood vessels. This study aims to  determine the  relationship  between the  number of mastocyt pherivascular and diameter of blood vessels.  This research is  in  vivo  exploratory  research  in    Wistar  rat  mesentery which was sensitated  with ovalbumin.  The  diameter  of blood  vessels  at  mesentery  preparate  were  measured  microscopically  using  a  micrometer  scale  standards.  At large  diameter  of  blood  vessels   (2.860  ±  0.348),  the  number  of  mastocyt was 12.3  ±  2.3.  At  medium diameter of blood vessel (1.276 ± 0.198), the  number of mastocyt was 4.4 ± 0.5. Blood vessels with small diameter (0.961 ± 0.043), the  number of mastocyt was 3.5 ± 1.3. Calculations area on the  microscope visual field  was divided into  four  areas (counting area), there  were zone 1, zone 2, zone 3 and zone 4. Statistical analysis showed  that  the  correlation  between  the  number  of  mastocyt  at   zone  1  and  the  diameter  of  blood  vessels  was 0,904 at 1% significance level.  Similar to  that  at zone 2 (r=0,892),  zone 3 and zone 4 (r=0,940).  We conclude there  was  a  significant  relationship  between  the  number  of  mastocyt  and  the  diameter  of  blood  vessels. Keywords:  mastocyt  pherivascular,  diameter  of  blood  vessels